Conditional admission, religious exemption type, and nonmedical vaccine exemptions in California before and after a state policy change. Issue 26 (18th June 2018) - Buttenheim, Alison M.; Jones, Malia; Mckown, Caitlin; Salmon, Daniel; Omer, Saad B.
Abstract: Recent measles and pertussis outbreaks in the US have focused national attention on state laws governing exemptions from mandatory vaccines for school entry. After several years of increases in nonmedical exemptions in California, the state assembly passed Assembly Bill 2109 in 2012, making nonmedical exemptions more difficult to obtain by requiring parents to obtain a signature from a health care provider. We used data from the California Department of Public Health to describe changes in the overall prevalence of personal belief exemptions and compositional changes in immunization status for the school years 2012–2013 through 2015–2016. Following the implementation of Assembly Bill 2109, the statewide exemption rate declined from 3.1% in 2013 to 2.5% in 2014 and then to 2.3% in 2015, representing a 25% reduction from the 2013 peak. Continued surveillance of exemption rates and vaccine refusal are needed to monitor and protect herd immunity against vaccine-preventable diseases.